Despacho ótimo de pequenas centrais hidrelétricas para minimização da contratação do suprimento - Malaquias, Luciano (2013)
This Master s Dissertation presents the development of a methodology to optimize the modulation of dispatch of Small Hydro Power Plants (SHPs). The main objective is to minimize the cost of supplying contracts, which comprise both the contracts of energy and the contracts of the use of the transmission and distribution systems by the power utilities. The application of the proposed methodology is technically subject to the operative constraints of the SHPs as well as to the constraints of the substations located in the connection points among utilities and the transmission system. The methodology is also based on the regulation of the Brazilian electrical system. The flow duration curves are taken in order to optimize the dispatch and the load curves from periods of the highest annual demands are considered to represent the distribution system behavior. We used the technique of genetic algorithms to the simulations with real data, from a Brazilian power utility are applied in order to analyze the economic and technical results and then proven the methodology.